2018
DOI: 10.1186/s40644-018-0163-7
|View full text |Cite
|
Sign up to set email alerts
|

Castleman disease versus lymphoma in neck lymph nodes: a comparative study using contrast-enhanced CT

Abstract: BackgroundThe purpose of this study was to determine the contrast-enhanced CT characteristics for differentiating between Castleman disease (CD) and lymphoma in neck lymph nodes.MethodsThis retrospective study evaluated the number (solitary or multiple), strength of contrast-enhancement, type of contrast-enhancement, surrounding vessels, contrast-enhanced Hounsfield unit (HU) values, and anatomical distributions of lymph nodes in 34 patients with confirmed CD and 55 patients with newly diagnosed untreated lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Previous studies reported that TNM stage[ 1 , 3 , 6 , 19 ] and adjuvant therapy[ 8 , 12 , 13 ] of esophageal NEC were closely related to the risk of death in patients with esophageal NEC, which is partly consistent with our findings. Studies also confirmed that earlier clinical stage tends to yield better survival outcomes for esophageal NEC[ 8 , 12 , 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies reported that TNM stage[ 1 , 3 , 6 , 19 ] and adjuvant therapy[ 8 , 12 , 13 ] of esophageal NEC were closely related to the risk of death in patients with esophageal NEC, which is partly consistent with our findings. Studies also confirmed that earlier clinical stage tends to yield better survival outcomes for esophageal NEC[ 8 , 12 , 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…In terms of diagnostic tests, contrast-enhanced, whole-body computed tomography (CT) is the standard for CD diagnosis with a sensitivity and specificity of 89 % and 94 %, respectively [ [21] , [22] , [23] , [24] , [25] ]. The affected nodes in CD typically show homogenously intense contrast enhancement; however, this finding is nonspecific.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies cite the thorax, specifically the mediastinum, as the most commonly involved site in CD [ 64 , 65 ]. Less commonly, there is involvement of the neck, abdomen/pelvis, and axilla.…”
Section: Ucdmentioning
confidence: 99%
“…On CT, UCD manifests as a well-circumscribed solitary enlarged lymph node or multiple nodules [ 65 ]. The nodes are larger than those of MCD and can go on to form a solid mass.…”
Section: Ucdmentioning
confidence: 99%